ダイ 26 ジ ナンキョク チイキ カンソク タイ ニ オケル ライダー ヲ モチイタ キョクイキ チュウソウ タイキ カンソク ケイカク - 野村, 彰夫; ノムラ, アキオ; 岩坂, 泰信; イワサカ, ヤスノブ; 福西, 浩; フクニシ, ヒロシ; 鹿野, 哲夫; カノ, テツオ; 平澤, 威男; ヒラサワ, タケオ; 川口, 貞男; カワグチ, サダオ; et al. (1985)
P(論文) 昭和基地において第26次南極地域観測隊(1984-1986)で実施する, ライダーによる中層大気観測計画について記述する。この観測は, 国際中層大気観測計画(MAP)の一環として計画されたものである。既に第24次観測隊(1984年)では, ルビーレーザーを用いて, 成層圏下部のエアロゾル観測を実施した。今回は, 新たに染素レーザーを用い, 中間圏上部でのナトリウム層の時間・空間変動観測, および成層圏上部から中間圏までの領域の温度分布観測を実施する。 A plan is described for lidar observations of the middle atmosphere which will be made by the 26th Japanese Antarctic Research Expedition, 1984-1986 (JARE-26) at Syowa Station (69°00′S, 39°35′E). This work has been planned as part of the Middle Atmosphere Program (MAP). The objectives of observation are to obtain the temporal and spatial variations of the sodium atomic layer in the upper mesosphere and those of temperature profile in the range from the upper stratosphere to the mesosphere by a tunable dye laser in addition to the aerosol observation in the lower stratosphere by a ruby laser which has been already started by the JARE-24 since 1983. departmental bulletin paper